O ensino da leitura e práticas de formação de leitores na escola primária de Santa Teresa (ES) na década de 1960 - Vago, Eliete Aparecida Locatelli (2013)
This research aimed to investigate the teaching of reading and training practices of readers in Santa Teresa Elementary School (ES), in the 1960s. It is characterized as a search for documentary stamp, guided by theoretical and methodological principles of Cultural History. Therefore, we made use of documentary sources as pedagogical meeting minutes, meeting minutes of the Câmara Municipal, official correspondence, laws, reports of government, messages, textbooks, guided materials for the school (federal and estadual), tests and notebooks of students, among other objects produced by different legislators and professional staff of the Teresense primary school. To read and analyse the documental corpus we dialogue with categories / concepts as: representation, practice, appropriation, strategies and tactics taken from the conception of authors as Michel de Certeau and Roger Chartier. The analysis of the sources taken during the process of writing this paper possible to infer that circulated in the city of Santa Teresa (ES) in the 1960 materials and methods that put the global method in vogue, considered the most suitable for the agents responsible for education policy for teaching reading in that space / time. In contrast, by addressing the appropriations that were made of these materials and methods in the educational practices of Teresense primary school, we realized the use of materials and methods that were opposed by the prescribed officer, enforcing the permanence of teaching reading by the traditional methods keeping tensions between the prescribed and practiced. Thus, we realized that other ways of teach reading and the writing, resisted and gained autonomous life in the routine of teachers in Teresense primary school. Regarding the profile of the reader that these practices have allowed school graduate, noticed an inclination of Teresense primary school for teaching reading based on textbooks, whose training was focused on the moral and civic values, capable of forming a citizen with a national character instilled good habits compatible with social life reflected in that moment of history.